การวิเคราะห์ตัวแปรจำแนกกลุ่มพยาบาลวิชาชีพที่คงอยู่ในงานโรงพยาบาลรัฐบาลและโรงพยาบาลเอกชน เขตกรุงเทพมหานคร - นิชนันท์ ฟุ้งลัดดา (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The purpose of this research was to determine the variable discriminating professional nurses job retention, governmental hospitals and private hospitals, Bangkok metropolis. Data were collected from 300 professional nurses job retention. The number of professional nurses in governmental hospitals and private hospitals was 150 in each group. Three main steps were conducted. The first step was to conduct for research framework concept by literature review and interviewed through semi-structured format. A total of 8 professional nurses participated for interview. Of these, 4 were professional nurses in governmental hospitals and 4 were professional nurses in private hospitals, who worked in that hospital more than 5 years. The second step was to develop the questionnaire. The questionnaire was judged to be acceptable by the panel of experts. The third step was collecting data. The research instrument consisted of the questionnaire. A total of completed questionnaires were 300 which was 100 percent of the total questionnaires. The data were analyzed by using discriminant analysis with stepwise method. Research findings were as follows: 1. The 3 variables discriminating professional nurses job reterntion, governmental hospitals were benefits, interpersonal relationship and age. The 4 variables discriminating professional nurses job retention, private hospitals were work environment and safety, convenience to commute, compensation and career advancement. 2. The percent correctly discriminant function professional nurses job retention, governmental hospitals and private hospitals were 94.0 and 96.0 percent respectively. The average percent correctly function was 95.0. The discriminant function was as follow: Z = .710 (BENEFITS) + .507 (INTERPERSONAL RELATIONSHIP) -.382 (WORK ENVIRONMENT AND SAFETY) -.336 (COMPENSATION) -.215 (CONVENIENCE TO COMMUTE) + .183 (AGE) - .182 (CAREER ADVANCEMENT.